Assessment and Mitigation of CRISPR‐Cas9‐Induced Nontargeted Translocations - Zhiyang Hou; Qiyi Yi; Mengying Wu; Lijun Wu; Fanghua Li; Ting Wang; Po Bian (Advanced Science)
Abstract The performance of CRISPR‐mediated genome editing near inverted repeats (IRs) potentially results in chromosomal translocations and other catastrophic rearrangements. However, the extent of this risk may be significantly underestimated because current reporter systems focus solely on site‐specific translocations. Here, trans‐acting reporter systems in Escherichia coli are developed to detect nontargeted translocations. Markedly increased frequency of translocations following CRISPR‐Cas9 activation is observed, with the magnitude determined primarily by the length of the IRs and the proximity between Cas9 target sites and IRs. These translocations arise through a combination of intramolecular single‐strand annealing and alternative end‐joining mechanisms. Furthermore, it is discovered that introducing segments homologous to IR loci can substantially mitigate nontargeted translocations without significantly compromising CRISPR‐Cas9‐mediated editing. The study provides valuable insights into the genetic risks associated with CRISPR technologies and suggests a viable strategy for developing genetically safer CRISPR systems.